Understanding the gap analysis towards quality services provided by AWC Facility Solutions Berhad / Noradibah Mohd Ajid - Mohd Ajid, Noradibah (Faculty of Business and Management, 2008)
This research is about a study of understanding the gap analysis towards quality services provided by AWC Facility Solutions Berhad by analyzing service quality gaps model. These includes gap 1 until gap 4 which includes management perception differences with customer's perception, external communications issues, and perceived and expected service values, are the factors that used to identify in order to investigate whether or not these factor exists within service quality delivered. The survey is conducted at USJ 9, Subang Jaya specifically the customer that use the service provided by AWC. The sample size for this study is 50 respondents. There were 50 questionnaires being distributed and completed. Data obtained using two methods that are primary and secondary data. Respondents are required to answer the questionnaires that contain element that potentially have relationship with customer's perceptions and the actual services delivered to them. Data are analyzed using Reliability Test, One Way Anova, Frequency Analysis, and Descriptive statistics through SPSS program. The result shows that all gaps in the service quality gaps model have significant relationship with the service provided by AWC.